Tratamento de sementes de soja com fungicidas para controle da ferrugem asiática da soja - Costa, Adriana de Fátima da (2007)
A trial was done in a greenhouse at Fazenda Capim Branco Universidade Federal de Uberlândia MG to evaluate different soybean fungicide treatments to reduce the progress of soybean Asian rust in its initial development stage. The experimental desing was completely randomized, as a factorial with 12 fungicides, 4 doses and 3 repetitions, in a total of 144 experimental units, for 5 cultivars. Each unit consisted of 1 line of 6 cells of a Styrofoam tray ( speedling type). The seeds of the five soybean cultivars (Conquista, Luziania, Monsoy 8329, Valiosa and UFUS Impacta) were treated with 0, 30, 40 or 50g i.a.-1 100Kg seeds-1 of the fungicides (Azoxistrobina 250g i.a., Ciproconazol 100g i.a., Ciproconazol + Azoxistrobina 280g i.a., Ciproconazol + Propiconazol 330g i.a., Difeconazole 250g i.a., Epoxiconazole + Pyraclostrobin 183g i.a., Fluquinconazole 167g i.a., Fluquinconazole 250g i.a., Propiconazole 250g i.a., Tebuconazole 200g i.a., Trifloxistrobina + Ciproconazol 267,5g i.a., Trifloxistrobina + Tebuconazole 300g i.a.). After the 2nd trifolium was expanded (35 days after sowing), the fungus was inoculated. Evaluations of the number of pustules per square centimeter (in the 3rd trifolium), plant height, soybean Asian rust severity, according to the scale proposed by Juliatti e Polizel (2004) were done at 42, 49 and 56 days after sowing. After the last evaluation, one plant was harvested per plot to count the number of de Bradyrhizobium japonicum nodules per root. The data obtained for severity and number of pustules were subjected to the analysis of area under the disease progress curve (AUDPC). Analysis of variance by the F test was done for all variables, and the averages were compared by Scott Knott test, at 5% probability. The seeds treated with Ciproconazol, Ciproconazol + Propiconazol and Propiconazol presented lower development. Ciproconazol and Ciproconazol + Propiconazol used in the treatment of seeds don't present selectivity to the bacteria Bradirhizobium sp.. The increase in the doses of active ingrident reduced the initial development of the plants until 56 days after sowing.